G-quadruplex recognition by the yeast telomere binding protein Rap1 - Traczyk, Anna (2019)
Although biochemical and structural studies have shown that DNA can adopt various conformations other than the canonical right – handed double helix, such structures were thought to be in vitro artifacts. It has been known for decades, that single stranded guanine – rich DNA can fold into a structure called G – quadruplexes. Those structures arise from guanine self – association through Hoogsteen hydrogen-bonds into planar quartets that are further stabilized by stacking on top of each other. Remarkably, recently these non-canonical secondary DNA (or RNA) structures have drawn much attention, as there is accumulating evidence in literature pointing towards the existence of G-quadruplex structures in vivo, suggesting their function as nucleic acid based regulatory mechanism and possible drug targets. Together with more evidence of the existence of G – quadruplex structure in cells, the proteins that might be involved in their regulation has been discovered. Over 20 years ago, the major telomere binding protein in budding yeast called Rap1 was shown to be able to bind to the single stranded telomeric G-overhangs and promote the formation of the G- quadruplex structures in vitro. Even though it has been more than two decades since this discovery, understanding of its consequence in vivo remains limited. The results presented in this dissertation help to better understand this interaction through determination of three – dimensional structure of the Rap1 DNA binding domain in complex with G – quadruplex DNA. Furthermore, I explore the possible function of this interaction in vivo as well as the involvement of Rap1 in the regulation of the TElomeric Repeat-containing RNA (TERRA) transcript.